ERNEST HEMINGWAY'S "CAT IN THE RAIN" (Ta'limning zamonaviy transformatsiyasi, 2024)
Ernest Hemingway's short story "Cat in the Rain," first published in 1925 in his collection "In Our Time", is an evocative work of emotional isolation and unlimited desires within a marriage. Against the backdrop of an Italian hotel, the narrative centers around an American couple, with the wife's simple wish to rescue a cat becoming a powerful symbol of her deeper emotional needs. This essay finds the story by studying into the characters' psyche deeper, the symbolic use of the cat, and the emotional acts that Hemingway notices through his minimalist writing style.